Bioprocess development for the production of novel oleogels from soybean and microbial oils. (December 2019) - Papadaki, Aikaterini; Kopsahelis, Nikolaos; Mallouchos, Athanasios; Mandala, Ioanna; Koutinas, Apostolis A.
Abstract: This study presents the production of novel oleogels via circular valorisation of food industry side streams. Sugarcane molasses and soybean processing side streams (i.e. soybean cake) were employed as fermentation feedstocks for the production of microbial oil. Fed-batch bioreactor fermentations carried out by the oleaginous yeast Rhodosporidium toruloides led to the production of 36.9 g/L total dry weight with an intracellular oil content of 49.8% (w/w) and 89.4 μg/g carotenoids. The carotenoid-rich microbial oil and soybean oil were evaluated as base oils for the production of wax-based oleogels. The wax esters, used as oleogelators, were produced via enzymatic catalysis, using microbial oil or soybean fatty acid distillate as raw materials. All oleogels presented a gel-like behaviour ( G′ > G″ ). However, the highest G′ was determined for the oleogel produced from soybean oil and microbial oil-wax esters, which indicated a stronger network. Thermal analysis showed that this oleogel had a melting temperature profile up to 35 °C, which is favorable for applications in the confectionery industry. Also, texture analysis demonstrated that soybean oil-microbial oil wax oleogel was stable (1.9–2.2 N) within 30-days storage period. This study showed the potential of novel oleogels production through the development of bioprocesses based on the valorisation of various renewable resources. Graphical abstract: Unlabelled Image Highlights: Molasses and soybean cake could be used for microbial oil and carotenoids production. Rhodosporidium toruloides produced 18.4 g/L microbial oil from crude feedstocks. Microbial oil accumulation coincided with 89.4 μg/g carotenoids production Soybean oil & microbial oil were successfully utilized for oleogels production.